Strategic Framework for Enhancing Mathematical Understanding in Young Learners - E. Odiri Onoshakpokaiye; Voke Eyetan (Journal of Early Childhood Development and Education, 2026)
Background: It is crucial for the development of fundamental mathematical ideas in early infancy. Empirical studies emphasize how play-based learning, cognitive preparedness, and contextual influences kids' mathematical reasoning. This roadmap provides educators and policymakers with guidance on how to promote successful math comprehension by synthesizing insights from previous studies. The early years are a critical time for developing fundamental mathematical knowledge. Objective: The study examines the Strategic Framework for Improving Young Learners' Mathematical Understanding. Methods: The study utilized a qualitative method where some related literature on the subjects were reviewed and analyzed to gain an insight into the topic. Results: The study finds that critical cognitive abilities including pattern identification, classification, and numerical comparison are necessary building blocks for procedural fluency and problem-solving. One of the main conclusions highlights how play-based learning promotes curiosity and more in-depth conceptual immersion. Moreover, the incorporation of reflective practices, explicit discourse, and interactive technologies improves children's capacity to express and develop mathematical concepts. Conclusion: Math learning outside of the classroom has been demonstrated to be enhanced by inclusive and culturally sensitive surroundings, as well as by parental and community involvement. Collectively, these observations highlight how crucial comprehensive, research-based methods of teaching mathematics at a young age are.